Regional Competitiveness in Latin America: A Comparative Study of the Key Elements for Regional Performance - Sergio Andrés González Catalán (Investigaciones Regionales - Journal of Regional Research)
Cross-country comparison is critical to understand the success of some regions and the stagnation of others in Latin America. This study measures regional competitiveness using a set of comparable regional indicators for Chile, Colombia, and Mexico in the 2008-2017 period and through a model that separates input competitiveness from results competitiveness (Aiginger and Firgo, 2017). The measurement allows comparison of regional competitiveness across countries. Results show that high regions with higher input competitiveness yield higher progress in competitiveness results for the studied period and that competitiveness capabilities play a major role in population well-being.